2010
DOI: 10.4314/wajm.v28i5.55003
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and its Response to Treatment with Recombinant Human Erythropoietin in Chronic Kidney Disease Patients

Abstract: BACKGROUND: The introduction of erythropoietin has transformed the management of anaemia in CKD, with considerable benefits which includes enhanced quality of life, increased exercise capacity and improved cardiac function. There is paucity of data on the beneficial effects of this treatment from this environment. OBJECTIVE: The aim of this work was to study the pattern and response of anaemia and its response to treatment with recombinant human erythropoietin(r-HuEpo) in CKD patients in Nigeria. METHODS: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…The higher prevalence of anemia in our study was within the range of figures reported in similar groups of patients elsewhere 2,3,[13][14][15] . However, the predominantly microcytic and hypochromic patterns could be explained either by the inflammatory state associated with chronic infection or by the presence of context specific factors (not investigated) such as nutritional deficiencies, hemoglobinopathies and parasitic diseases 7,8 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The higher prevalence of anemia in our study was within the range of figures reported in similar groups of patients elsewhere 2,3,[13][14][15] . However, the predominantly microcytic and hypochromic patterns could be explained either by the inflammatory state associated with chronic infection or by the presence of context specific factors (not investigated) such as nutritional deficiencies, hemoglobinopathies and parasitic diseases 7,8 .…”
Section: Discussionsupporting
confidence: 77%
“…Our study also has some strengths in the sense that it provides a unique picture, which, in this setting can potentially contribute to raise more attention on anemia, a leading condition in people with CKD. It revealed the positive correlation between hematological profile and erythropoietin and IV iron therapy in a few patients receiving these therapies, even in non-optimal dose, due to financial constraints as reported in similar setting 14,15 . Our efforts in tracking a large number of our participants during follow-up provides some indicators of the burden of anemia in chronic hemodialysis patients and the outcome of anemia correction approaches in the context of limited access to ESA and intravenous iron therapies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Prevalence of anemia in CKD stage 1 is 31.2% and 93.3% in CKD stage 4 and 5. [6][7][8][9][10][11][12] Erythropoietin is a hormone produced by per tubular capillaries of kidney that promotes red blood cells production (erythropoiesis) from bone marrow by increasing proliferation and maturation of erythroidprogenitors. 13 Use of exogenous erythropoietin in CKD improves hemoglobin level, reduces risk of cardiovascular disease, and improves patient wellbeing and exercise tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The condition is defined, in adults and children older than 15 years with CKD, as hemoglobin (Hb) concentration < 13.0 g/dl (< 130 g/l) in males and < 12.0 g/dl (< 120 g/l) in females [2]. Studies conducted elsewhere have reported differing prevalence and factors associated with anemia in ESRD patients [8][9][10][11][12][13] Despite the high burden of ESRD and its complications in Sudan, there is a scarcity of published information regarding the prevalence of, and risk factors for, anemia in people with ESRD in the country. The study provides baseline information about the status of anemia in ESRD patients undergoing HD in Khartoum State and the factors affecting the control of Hb levels.…”
mentioning
confidence: 99%